Biotin/Folate‐decorated Human Serum Albumin Nanoparticles of Docetaxel: Comparison of Chemically Conjugated Nanostructures and Physically Loaded Nanoparticles for Targeting of Breast Cancer. (31st August 2015) - Nateghian, Navid; Goodarzi, Navid; Amini, Mohsen; Atyabi, Fatemeh; Khorramizadeh, Mohammad Reza; Dinarvand, Rassoul
Abstract : Docetaxel (DTX) is a widely used chemotherapeutic agent with very low water solubility. Conjugation of DTX to human serum albumin (HSA) is an effective way to increase its water solubility. Attachment of folic acid (FA) or biotin as targeting moieties to DTX‐HSA conjugates may lead to active targeting and specific uptake by cancer cells with overexpressed FA or biotin receptors. In this study, FA or biotin molecules were attached to DTX‐HSA conjugates by two different methods. In one method, FA or biotin molecules were attached to remaining NH2 residues of HSA in DTX‐HSA conjugate by covalent bonds. In the second method, HSA‐FA or HSA‐biotin conjugates were synthesized separately and then combined by DTX‐HSA conjugate in proper ratio to prepare nanoparticles containing DTX‐HSA plus HSA‐FA or HSA‐biotin. Cell viability of different nanoparticle was evaluated on MDA‐MB‐231 (folate receptor positive), A549 (folate receptor negative), and 4T1 (biotin receptor positive) and showed superior cytotoxicity compared with free docetaxel (Taxotere ® ). In vivo studies of DTX‐HSA‐FA and DTX‐HSA‐biotin conjugates in BULB/c mice, tumorized by 4T1 cell line, showed the conjugates prepared in this study were more powerful in the reduction in tumor size and increasing the survival rate when compared to free docetaxel. Abstract : The aim of this study was to use the advantage of both EPR effect and active targeting of nanoparticles using targeting moieties to increase the specific uptake of the drug delivery system by cancer cells. The results showed that the antitumor effect of these conjugates was much greater than the free drug and survival time in longer as well. Thus, they might be promising drug delivery systems for cancer treatment which may develop their manufacturing method for large‐scale production.